A Literature Review on College Choice and Marketing Strategies for Recruitment. (December 2014) - Han, Pingping
<x xml:space="preserve">Abstract</x> Recruiting enough qualified students is becoming an important topic for colleges and universities as the competition within the higher education market intensifies. Knowing the reasons prospective students choose which institution to attend is essential to develop effective marketing and recruiting strategies. The purpose of this study is to present current research and literature on the factors influencing the college choice process and marketing practices in recruiting.